(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The spectrum of acute hepatitis B (HBV) infection, typically defined as the first six months post-exposure, ranges from asymptomatic infection and mild self-limiting illness to severe icteric hepatitis and rare fulminant liver failure. Most adults recover completely, though infants and children are more likely to develop chronic, lifelong infection. There is limited data regarding progression of acute hepatitis B virus (HBV) infection to chronic phase. Aim: To determine the percentage of patients of acute hepatitis B who progressed to chronic hepatitis B stage. Material and methods: It was a prospective study over a period of ten years in which total 1000 confirmed acute hepatitis B patients were enrolled but out of them complete data pertaining to 697 patients, (481 men and 216 women, 04–82 years old) was available. Hence, these patients were taken up in final analysis. Results: Out of total of 697 acute hepatitis B patients, 658 patients resolved and became Hepatitis B surface antigen (HbsAg) and Hepatitis B virus DNA negative whereas 39 patients went into chronic phase. The progression into chronic phase was not dependent upon gender of patient, as results were comparable in both the groups. However, Serum Bilirubin, Serum amino transaminases, HbeAg and HBV DNA Quantitative levels were significantly lower in patients who progressed to chronic hepatitis stage. Conclusions: The chronicity rate in overall pool of 697 patients was 5.59 % and on analysing for male and female group it was 5.61% and 5.55% respectively, meaning by almost comparable results in both the groups. Out of 27 males who went into chronic phase, 20 behave as inactive carriers and 7 required continued antiviral therapy. In 12 females who went into chronic phase, 10 behaved as inactive carriers and only two required antiviral therapy. The minimal representation from below 14 years of age group tell about the success and effectivity of hepatitis B vaccination (HBV) which is part of universal immunization in India for last 14 years. The majority of patients who advanced in chronic phase had mild hepatitis on comparison to patients who resolved, thus suggesting that patients with mild acute hepatitis B infection may have a higher risk of progressing to chronic infection.